Design Requirements for Group-IV Laser Based on Fully Strained Ge1−xSnx Embedded in Partially Relaxed Si1−y−zGeySnz Buffer Layers. (1st January 2016) - Shimura, Yosuke; Srinivasan, Srinivasan Ashwyn; Loo, Roger
Abstract : Theoretical calculation using the model solid theory is performed to design the stack of a group-IV laser based on a fully strained Ge1−x Snx active layer grown on a strain relaxed Si1−y−z Gey Snz buffer/barrier layer. The degree of strain relaxation is taken into account for the calculation for the first time. The transition between the indirect and the direct band material for the active Ge1−x Snx layer is calculated as function of Sn content and strain. The required Sn content in the buffer layer needed to apply the required strain in the active layer in order to obtain a direct bandgap material is calculated. Besides, the band offset between the (partly) strain relaxed Si1−y−z Gey Snz buffer layer and the Ge1−x Snx pseudomorphically grown on it is calculated. We conclude that an 80% relaxed buffer layer needs to contain 13.8% Si and 14% Sn in order to provide sufficiently high band offsets with respect to the active Ge1−x Snx layer which contains at least 6% Sn in order to obtain a direct bandgap.